Analisis perilaku perawat dalam pencegahan pengendalian kejadian plebitis di rumah sakit : literatur review - Emerita, Emerita; Suryani, Lilis (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Objective: Some evidences found in the world related to Phlebitis case, influence the controlling and preventing infection in the hospital. Phlebitis case in a hospital is a quality standard of hospital service. The effort to increase the quality standart of hospital needs nurse's good behaviour (knowledge, act, skill) in giving nursing treatments especially on infusion installation and maintenance.These behaviour has a very meaningful connection with the application of preventing and controlling infection in the hospital.Methods: This literature review has structural purpose, which is to identify, to evaluate and to synthesize the best evidence whish is available in the world, including in Indonesia. The nurse's behaviour can give an impact for the quality standart service in hospital. Pubmed, Google Scholar or scientist EBSCO and being acceed to find a prove about nurse's behaviour and Phlebitis by using ‘behaviour’ OR ‘attitude’ OR ‘knowlegde’ OR ‘obedience’ AND ‘phlebitis’ OR ‘intravenous therapy’ OR ‘dreassing of infusion’ AND ‘standart precaution’ OR ‘nosocomial infection’ as a key words.Results: The first step to looking the articles is by defind the keywords ‘behaviour’ OR ‘attitude’ OR ‘knowlegde’ OR ‘obedience’ AND ‘phlebitis’ OR ‘intravenous therapy’ OR ‘dreassing of infusion’ AND ‘standart precaution’ OR ‘nosocomial infection’, we got 112627 articles, Google Scholar or scientis, we got 58 articles, EBSCO we got 764 articles. The second step we sorted the articles from the previous step by using ‘publication date 5 years, abstract, full text availability, as a key words. And by Pubmed we got 26263 articles, Google Scholar or scientist we got 36 articles, EBSCO we got 112 articles. The next step is by sorting the result of the previous step by filted articles attributes (peer reviewed) for Pubmed we got 467 articles, Google Scholar or scientist we got 27 articles, EBSCO we got 34 articles. Next, by sorting using criteria Inclusion (behaviour,attitude,knowlegde), phlebitis and exclusion criteria (vena central line) then we got 9 articles from Pubmed, 19 articles from Google Scholar or scientist , 2 articles from EBSCO.Conclusion: The effort of controlling and preventing infection in the hospital can be done by applying universal caution on Phlebitis case, for example on intravena installation theraphy, needs the nurse that has knowledge, act and skill on intravena installation.